O ethos no discurso político de Dilma Rousseff : a imagem da mulher na política - Seno, Ana Regina (2014)
The purpose of this study is to analyze the female-voice political discourse under the perspective of the French-line discourse analysis (DA) in 4 selected speeches by Brazilian president Dilma Rousseff, using contributions of Dominique Maingueneau’s and Patrick Chareaudeau’s. This inquiry is centered on the ethos’ analysis after the notions by both theoreticians for the identification of the characteristics of the female-voice enunciator’s political discourse. Out of Maingueneau’s studies, besides the notion of discursive ethos, the categories of interdiscourse and enunciation scenes are used, especially the scenographies constituted in those speeches. Out of Charaudeau’s researches, we privileged the notions of ethos, charisma, and pathos applied to the political discourse, seeking to characterize the way of being and saying of the enunciating subject, revealed through the discursive patemization. Although both researchers have different theoretical-methodological ground proposals, the complementing points of approach are looked for in order to characterize the female-voice discursive ethos. The analytical proceedings are preceded by a brief history of the trajectory, participation, and presence of woman in national and international politics, mainly in the 20th and 21st centuries, in order to compose the present social-historical scenario, given the inedited and relevant fact of the election of the first female president of Brazil. The main discussions involve the macro- and micro-themes of the selected speeches, their scenographies constituted therein, highlighting the marks that influence ethos characterizations, including the ones proposed by Chareaudeau, like of authority, accountability, seriousness, and courage. Linked to those aspects that help to characterize the ethos, also the components of the discursive memory are analyzed, articulating them with the discursive formations of the respective discursive fields. Finally, the analyses undertaken are synthesized, detailing the repercussion on the image of woman in politics and disserting about the female-voice enunciator ethos in the political discourse.